PROSES KREATIF LILI SUPARLI DALAM MENGEMBANGKAN WAYANG CATUR - Ningsih, Reina Y. Puspita (Paraguna, 2021)
This study discusses the creative process of Lili Suparli in developing wayang catur. Wallas's theory is used to explore the development of a particular creative process. Suparli is one of the Sundanese gamelan maestro who presents many works in Sundanese art. The purpose of this study is to describe the creative process that is passed by a creator in making works. This theory has four stages: incubation, illumination, preparation, and verification. This study employed observation and described the phenomenon. The result shows that Suparlis creative process has spanned over a long period. Several internal factors (intuition, motivation, and imagination) and external factors (formal-and-informal education, family, and environment,) influence his creative process. The knowledge and experiences obtained through his daily life form his artwork's character and quality. In this context, they manifest as an innovative art called wayang catur plus. That way the creative process is always passed by a creator in making his work.